Cointegration and Regression Analyses as Alternative Methods to Verify the Protective Properties of Inflation Hedge Investments - Wolski, Rafał (Analizy kointegracji i regresji jako alternatywne metody weryfikacji właściwości ochronnych inwestycji zabezpieczających przed inflacją, 2024)
Aim: In the face of rising inflation, a variety of financial tools are increasingly important to protect capital from loss of value. This leads to questions about which investment to choose to protect capital from loss of value. The purpose of the work was to determine whether selected investment directions on the Polish capital market can protect capital against inflation-related loss of value. Methodology: The study used a cointegration analysis using the Engle-Granger test and a regression analysis using the OLS method. The research covered the period from Q4 2008 to Q4 2022, using the bond TBSP index, Bitcoin and gold, the WIG index, the WIG Real Estate stock index and the NBP hedonic index of property prices in the seven largest cities in Poland. These investments were related to the HICP harmonised inflation index published by the European Statistical Office (EUROSTAT). Findings: The analysis revealed different results depending on the survey methodology adopted. The co-integration analysis pointed to Bitcoin as an inflation hedging investment, whereas the regression analysis pointed to gold and residential property as inflation combined. Implications: The study enables a better understanding of the complex dynamics involved in preserving purchasing power during periods of high inflation. Originality/value: The study is an important contribution to filling the gaps in the Polish market in terms of analysis of capital protection options against inflation. Although the study focused only on the Polish market, this topic has not been addressed through a period of low inflation also in mature economies.
Financial Sciences. Nauki o Finansach, 2024, vol. 29, no. 2, s. 14-26
Keywords: investments; inflation hedging; portfolio; real estate; Poland; inwestycje; zabezpieczenie przed inflacją; nieruchomości; portfel; Polska